2019
DOI: 10.1021/acssuschemeng.9b00161
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose/Gelatin Composite Cryogels for Controlled Drug Release

Abstract: Nanocellulose/gelatin composite cryogels with controllable porosity, reversible network structure and good biocompatibility were constructed via the chemical cross-linking of dialdehyde starch and further used as the carriers for controlled 5-fluorouracil (5-FU) release. The pore structure of the composite cryogels was successfully tuned by changing the dosages and ratios of nanofibrillated cellulose (NFC), gelatin and dialdehyde starch. Under the same density of cryogels, increasing the NFC content results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 45 publications
0
65
0
Order By: Relevance
“…CNF was prepared according to previous work [31,32]. Five grams of bleached softwood pulp with mechanical pretreatment was suspended in 450 mL of deionized water and 50 mL of NaClO.…”
Section: Methodsmentioning
confidence: 99%
“…CNF was prepared according to previous work [31,32]. Five grams of bleached softwood pulp with mechanical pretreatment was suspended in 450 mL of deionized water and 50 mL of NaClO.…”
Section: Methodsmentioning
confidence: 99%
“…As biopolymeric materials from natural sources demonstrate great potential in biomedical, pharmaceutical, and environmental applications due to their biocompatible, biodegradable and non‐toxic structures. To the best of our knowledge, the synthesis of cryogel from natural polymers in the literature is very new and there only are few studies on cryogels from natural polymers 17,21,24,26 . To the best of our knowledge this is the first report for the synthesis and characterization of Inulin cryogels in the literature.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Demirci et al, reported the use of HA and HA based cryogel composites with polyethyleneimine and Halloysite nanotubes for sodium diclofenac (SDF) drug release studies and found that 31% to 87% of the loaded SDF was released in 20 hours 17 . In another study, Li et al; reported the cross‐linked nano fibrillated cellulose/gelatin (NFC) composite cryogels for 5‐FU, a cancer drug release studies via physical embedding this drug into cryogels due to hydrogen bond interaction 26 . And, the authors reported that the cumulative release of 5‐FU from the cryogels was close to 100% after 12 hours 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations